A Qualitative Study of Mental Health Problems among Children Displaced by War in Northern Uganda - Betancourt, Theresa Stichick; Speelman, Liesbeth; Onyango, Grace; Bolton, Paul (Transcultural psychiatry, 2009)
While multiple studies have found that children affected by war are at increased risk for a range of mental health problems, little research has investigated how mental health problems are perceived locally. In this study we used a previously developed rapid ethnographic assessment method to explore local perceptions of mental health problems among children and adults from the Acholi ethnic group displaced by the war in northern Uganda. We conducted 45 free list interviews and 57 key informant interviews. The rapid assessment approach appears to have worked well for interviewing caretakers and children aged 10–17 years.We describe several locally defined syndromes: two tam/par/kumu (depression and dysthymia-like syndromes), ma lwor (a mixed anxiety and depression-like syndrome), and a category of conduct problems referred to as kwo maraco/gin lugero. The descriptions of these local syndromes were similar to western mood, anxiety and conduct disorders, but included culturespecific elements.
Keywords: Children and adolescents; Mental health; Qualitative research; Northern Uganda; War